Mathematic simulation of distillation column with infinite separation ability and various calculation sets - S. L. Nazanskiy; A. V. Solokhin; A. V. Kiyko; V. E. Obong (Тонкие химические технологии, 2013)
Different variants of calculation sets of the distillation column with infinite separation ability are investigated. With a ternary zeotropic mixture as an example the number of calculation sets is determined. Examples of rating and design calculation are given.